EVALUATION OF THE INFLUENCE OF THE QUALITY OF DITCH WATER IN THE CULTIVATION OF REPEATED CROPS - U. A. Juraev; O.U.Murodov; O. M. Yusupova (Bright Mind Publishing, 2025)
This article provides information on the effectiveness of using Nanosilicon and AMINOSID Universal Si biopreparations in the Bukhara oasis grassland, which is alluvial, moderately saline, medium-sandy in terms of mechanical composition, with a groundwater level of 2.0-2.5 meters and a mineralization of 2.5-3.0 g/l, and irrigated with low-mineralized zaur waters and the use of Nanosilicon and AMINOSID Universal Si biopreparations.
Keywords: Drainage waters, mineralization, biopreparation, Nanosilicon, AMINOSID Universal Si.